2020
DOI: 10.1007/s00431-020-03853-8
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for N-terminal Pro-brain natriuretic peptide in premature infants during their first weeks of life

Abstract: The aim of our study was to observe the temporal distribution of serum N-terminal pro-brain natriuretic peptide (NT-proBNP) in premature infants of ≤ 31 weeks of gestational age (GA) during the first weeks of life. NT-proBNP values of 118 preterm infants born ≤ 31 weeks GA were determined during the first week of life, after 4 ± 1 weeks of life, and at a corrected GA of 36 ± 2 weeks. Infants were divided into two groups: those without relevant complications and those with complications related to prematurity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…N-terminal pro b-type natriuretic peptide (NT-proBNP) is an inactive amino acid fragment of the brain natriuretic peptide (BNP) that is released from cardiomyocytes in response to pressure or volume overload, promoting vasodilation and natriuresis ( 10 ). NT-proBNP level is associated with impaired cardiac function among children and infants and influenced by kidney function ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-terminal pro b-type natriuretic peptide (NT-proBNP) is an inactive amino acid fragment of the brain natriuretic peptide (BNP) that is released from cardiomyocytes in response to pressure or volume overload, promoting vasodilation and natriuresis ( 10 ). NT-proBNP level is associated with impaired cardiac function among children and infants and influenced by kidney function ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…NT-proBNP level is associated with impaired cardiac function among children and infants and influenced by kidney function ( 11 13 ). In adults, NT-proBNP has been extensively studied in many domains including cardiac diseases, diabetes, and rheumatoid arthritis ( 10 , 14 ). Several studies found that NT-proBNP was associated with the hospital stay of adult patients with heart diseases ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study had noted that the levels of NT-proBNP were the highest in first days of life in full-term infants and showed a marked decline during the first week life. They noted that the reference values of NT-proBNP in infants and children var across wide ranges, 260-13,224 pg/mL and 28-7250 pg/mL, during days 0-2 and 3-11 life, respectively, and found that the level dropped dramatically after 3 days of life Harris et al and Fritz et al reported a similar phenomenon in preterm infants [8,9]. In t…”
Section: Discussionmentioning
confidence: 88%
“…They noted that the reference values of NT-proBNP in infants and children varied across wide ranges, 260-13,224 pg/mL and 28-7250 pg/mL, during days 0-2 and 3-11 of life, respectively, and found that the level dropped dramatically after 3 days of life [4]. Harris et al and Fritz et al reported a similar phenomenon in preterm infants [8,9]. In this study, we also found that, in preterm infants without reduced cardiac ejection fraction, the NT-proBNP levels declined gradually after birth.…”
Section: Discussionmentioning
confidence: 90%
“…They concluded that serum NT-proBNP levels during the first week of life are high and widely distributed in preterm infants and decrease subsequently to reach a distinctly lower and stable plateau at around 1 month of life. 44…”
Section: Discussionmentioning
confidence: 99%